Integration Analysis of m6A-SNPs and eQTLs Associated With Sepsis Reveals Platelet Degranulation and Staphylococcus aureus Infection are Mediated by m6A mRNA Methylation - Sun, Xuri; Dai, Yishuang; Tan, Guoliang; Liu, Yuqi; Li, Neng (Frontiers in Genetics, 2020)
Sepsis is a major threaten for critical patients with high mortality rate. Host immune system response to pathogen infection is critical biological processes involved in the onset and development of sepsis. It was suggested for a long time that heterogeneous host genome variation, especial single nucleotide polymorphisms (SNPs) contribute to the different disease process. However, the function of SNPs located in the no-coding region is remained to be elucidated. Recently, m6A modification level on mRNA is revealed different with SNPs. As m6A is a crucial regulator of gene expression, these SNPs could control genes through change the m6A level on mRNA. To identify the SNPs effected on gene expression through changing m6A level, we integrate the m6A-SNP and eQTLs in sepsis. Results showed 15720 m6A-cis-eQTLs and 381 m6A-trans-eQTLs in sepsis. Next, 1321 genes were identified as location site of m6A-cis-eQTLs. They are enriched in platelet and Staphylococcus aureus infection pathways, which are vital pathways involved in the pathophysiological process of sepsis. In conclusion, m6A modification on mRNA played a very important role in sepsis. m6A-cis-eQTLs has the most potential effect on the individual variation of sepsis progress.